Elevated serum hepcidin levels during an intensified training period in well-trained female long-distance runners - Ishibashi, A.; Maeda, N.; Sumi, D.; Goto, K. (Nutrients, 2017)
Iron is essential for providing oxygen to working muscles during exercise, and iron deficiency leads to decreased exercise capacity during endurance events. However, the mechanism of iron deficiency among endurance athletes remains unclear. In this study, we compared iron status between two periods involving different training regimens. Sixteen female long-distance runners participated. Over a seven-month period, fasting blood samples were collected during their regular training period (LOW; middle of February) and during an intensified training period (INT; late of August) to determine blood hematological, iron, and inflammatory parameters. Three-day food diaries were also assessed. Body weight and lean body mass did not differ significantly between LOW and INT, while body fat and body fat percentage were significantly lower in INT (p < 0.05). Blood hemoglobin, serum ferritin, total protein, and iron levels, total iron-binding capacity, and transferrin saturation did not differ significantly between the two periods. Serum hepcidin levels were significantly higher during INT than LOW (p < 0.05). Carbohydrate and iron intakes from the daily diet were significantly higher during INT than LOW (p < 0.05). In conclusion, an elevated hepcidin level was observed during an intensified training period in long-distance runners, despite an apparently adequate daily intake of iron